Difficulties facing the integration of people with motor disabilities in formal education at the basic stage - South Darfur (2018 – 2019) - Mohammed, Afaf Mohammed Ocasha; Ahmed, Mohmmed Ali Ahamed Mohmmed; Ezzedine, Awda Mohammed Osman (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to identify the difficulties facing the integration of motor disabilities in formal education at the basic stage in the state of South Darfur from the point of view of principals and teachers in the state of South Darfur. For the purposes of this study, the researchers followed the analytical descriptive approach, in addition to the case study methodology. In order to collect the information and data, the researchers relied on the observation tool in addition to the questionnaire distributed to a random sample of 29 principals and teachers of basic schools in South Darfur state. The data were analyzed statistically by the Statistical Package for Social Sciences (SPSS). The study came out with a number of results:The physically disabled are living a big problem because of the lack of the tools, equipment and auxiliary devices they need in school Movement disabled people believe that there is a very big problem because of the lack of appropriate school examinations to suit their abilities in terms of time, quantity and content. Persons with motor disabilities notice the deficiencies of the school in providing quality supervisory meetings for the physically disabledThe study recommended that: Raising the awareness of the community to show the advantages of integrating pupils with motor disabilities in the public schools in Nyala Central. Encourage increased opportunities for social interaction between students and disabled students. To apply the idea of ​​progressive integration of the disabled in the regular schools.
Keywords: Difficulties; Consolidation; Formal education; Physically disabled